A GUI Based Run-Time Analysis of Sorting Algorithms and their Comparative Study - Shastri, Sourabh; Mansotra, Vibhakar; Singh Bhadwal, Arun; Kumari, Monika; Khajuria, Avish; Singh Jasrotia, Dalbir (International Journal of Computer Sciences and Engineering, 2025)
The analysis of algorithms is a subject that has always arouses enormous inquisitiveness. It helps us to determine the efficient algorithm in terms of time and space consumed. There are valid methods of calculating the complexity of an algorithm. In general, a suitable solution is to calculate the run time analysis of the algorithm. The present study documents the comparative analysis of seven different sorting algorithms of data structures viz. Bubble sort, Selection sort, Insertion sort, Shell sort, Heap sort, Quick sort and Merge sort. The implementation is carried out in Visual Studio C# by creating a Graphical User Interface to calculate the running time of these seven algorithms.